2001
DOI: 10.1161/hc5001.101061
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin and the Risk of Cardiovascular Disease in the West of Scotland Coronary Prevention Study (WOSCOPS)

Abstract: on behalf of the WOSCOPS Executive CommitteeBackground-Leptin plays a role in fat metabolism and correlates with insulin resistance and other markers of the metabolic syndrome, independent of total adiposity. Therefore, we hypothesized that raised leptin levels may identify men at increased risk of a coronary event in the West of Scotland Coronary Prevention Study (WOSCOPS). Methods and Results-Plasma leptin levels were measured at baseline in 377 men (cases) who subsequently experienced a coronary event and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
539
6
32

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 767 publications
(618 citation statements)
references
References 34 publications
29
539
6
32
Order By: Relevance
“…However, in our study, CRP was significantly correlated with leptin concentrations. This association, which was not observed after adjustment for BF in multivariate regression analysis, is in agreement with previous studies [13,41,43] and suggests that, in addition to leptin, another factor altered in obesity may be involved in the obesityinduced increase in CRP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in our study, CRP was significantly correlated with leptin concentrations. This association, which was not observed after adjustment for BF in multivariate regression analysis, is in agreement with previous studies [13,41,43] and suggests that, in addition to leptin, another factor altered in obesity may be involved in the obesityinduced increase in CRP.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, plasma leptin concentrations are raised in patients with congestive heart failure [10] and correlate with heart rate in heart transplant recipients [11]. Moreover, some authors have proposed hyperleptinemia as a component of a metabolic syndrome of cardiovascular risk [12] while others have shown that leptin is an independent risk factor for coronary events in hypercholesterolemic men [13].…”
Section: Introductionmentioning
confidence: 99%
“…8,11,12 According to this, changes of leptin values correlated significantly to the changes of insulin resistance index (HOMA) in the 1-y period in multiple linear regression analysis adjusted for age, gender, and degree of overweight. The exact interaction between insulin and leptin are not fully elucidated.…”
Section: Discussionmentioning
confidence: 74%
“…SOB-R levels, which are decreased in obesity, 4,8,9 are postulated to play an important role in the pathophysiology of energy homeostasis. 6,10 Furthermore, not only associations between leptin and insulin resistance Fthe major complication of obesity determining morbidity and mortality [11][12][13] F but also the relationship between sOB-R and insulin resistance is being discussed. 14,15 Thus, understanding the regulation of circulating sOB-R in humans may have important physiological and therapeutical implications for human obesity and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…8 Accordingly, a strong association between leptin plasma levels and increased risk of myocardial infarction and stroke has been reported. 9,10 In the present study, we examined the Class I/Class II and the individual allele genotypes of the LEP-tet in patients screened for cardiovascular risk, to evaluate the role of this polymorphism as a marker for cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%